The Crisis of Brexit and Other Socio-Cultural Aspects of Silencing the Past through the Example of Anna Burns’ Milkman - Frątczak-Dąbrowska, Marta; Jarząb-Napierała, Joanna (Porównania, 2021)
The present article scrutinizes the phenomenon of a systemic silencing of the past visible in recent socio-political challenges caused by Brexit, especially in the case of the Irish border. Due to the comparative character of the paper, the attention is targeted at a symptomatic amnesia manifested on the British and Northern Irish sides. Postcolonial melancholia, to use Paul Gilroy’s term, facilitated by a systemic whitewashing of British imperial past, is contrasted here with Northern Irish postcolonial amnesia understood as a personal and institutionalised suppression of the difficult memory of colonisation and violence. In what follows, the paper aims to show how these two phenomena meet in the conflict of Brexit and how literature comments on the current political, social and cultural issues such as Brexit based on the example of Anna Burns’ novel Milkman (2018). The article discusses the silence which has surrounded the issue of the Irish Border in Brexit debates, as well as looks at the Northern Irish reluctance to talk about their past as an unsuccessful attempt to escape the demons of the past.